Dual-excitation and dual-emission carbon dots for Fe3+ detection, temperature sensing, and lysosome targeting. Issue 37 (1st September 2021) - Li, Xiaofeng; Bao, Yuejing; Dong, Xiaorui; Shi, Lihong; Shuang, Shaomin
Abstract : Dual-excitation and dual-emission carbon dots (CDs) have been prepared by simple one-step hydrothermal treatment of p -phenylenediamine and 5-aminosalicylic acid. Abstract : Dual-excitation and dual-emission carbon dots (CDs) have been prepared by simple one-step hydrothermal treatment of p -phenylenediamine and 5-aminosalicylic acid. The as-prepared CDs emit bright green fluorescence under excitation at 320–400 nm and bright orange fluorescence under excitation at 490–560 nm. Interestingly, the CDs can be employed as a dual-excitation and dual-emission fluorescent probe for Fe 3+ detection in aqueous solution and living cells. Furthermore, the obtained CDs can function as a promising dual-excitation and dual-emission temperature sensor. Additionally, the CDs can be utilized for lysosomal targeting.